(untitled) (Boletin Médico de Postgrado, 2022)
Preeclampsia is recognized as the most frequent medical complication related to pregnancy whose pathogenesis varies with different risk factors. Doppler velocimetry of the ophthalmic artery (DVOA) is an innovative study that evaluated in conjunction with the uterine arteries in the second trimester has proven to be a predictive test of high reproducibility. In order to determine the Doppler ultrasonography features of ophthalmic and uterine arteries in pregnant women with risk factors for preeclampsia, a descriptive cross-sectional investigation was carried out in 20 women between 18 and 24 weeks of pregnancy who attended the prenatal consultation of the Gynecology and Obstetrics Department of the Hospital Central Universitario Dr. Antonio Maria Pineda. Past history of prior preeclampsia is a risk factor for the development of subsequent preeclampsia observed in 50% of patients. 55% of pregnant women were overweight and 30% had obesity type I. Diastolic arterial pressure was high in 75% of patients. 65% ​​of patients had high uterine artery mean pulsatility index and presence of Notch. The diastolic hump in ophthalmic artery was observed in 60% of the patients. It is concluded that DVOA may indicate intracranial maternal hemodynamic changes even when patients do not exhibit the classic features of preeclampsia.